Performance of Selected Diploid Watermelon Pollenizers - J. H. Freeman; G. A. Miller; Stephen M. Olson (EDIS, 2007)
HS-1081, a 6-page fact sheet by J.H. Freeman, G. A. Miller, and S.M. Olson, provides growers with results and discussion of studies to determine the effectiveness of diploid watermelon cultivars as pollenizers for more popular triploid seedless watermelon crops. Includes references. Published by the UF Department of Horticultural Sciences, January 2007.